HUBUNGAN KARAKTERISTIK SOSIODEMOGRAFI DENGAN TINGKAT PENGETAHUAN DAGUSIBU OBAT ANTIBIOTIK PADA MASYARAKAT DI KELURAHAN BULU JEPARA - Laila Septania Rafi; Zaenal Fanani; Ulviani Yulia Husna (Yayasan Nusantara Hasana Berdikari, 2025)
Lack of knowledge about the antibiotic DAGUSIBU can lead to drug resistance. This occurs because inappropriate use of the drug, inappropriate dosage, and a lack of understanding of the indications of the drug being consumed can cause the drug to not work properly in the body, thus causing harm. Therefore, the risk of drug resistance is unavoidable. Age, gender, residence, education, and income are all contributing factors to the level of antibiotic knowledge. The purpose of this study was to determine the relationship between sociodemographic characteristics and the level of knowledge about the antibiotic DAGUSIBU among the community in Bulu Village, Jepara. This study used a correlational analysis design with a cross-sectional study approach. The sample for this study was 115 respondents aged 15-50 years old, selected using a purposive sampling technique. The obtained data were analyzed using a correlation test, namely the chi-square test. After testing, the results showed that sociodemographic characteristics based on gender, age, highest education, occupation, and income were significantly associated with the level of knowledge about the antibiotic DAGUSIBU among the community in Bulu Village, Jepara. Further research using a questionnaire method and supplemented with leaflet education is needed to assess the community's level of knowledge about the antibiotic DAGUSIBU, both before and after the education.